PENERAPAN KEGIATAN MENARI UNTUK MENGEMBANGKAN SENI ANAK USIA DINI DI BANJAR WANASARI DESA SULANGAI KECAMATAN PETANG KABUPATEN BADUNG - Putri Megawati Ade Olin; Aria Prima Dewi PF Kadek; Yeni Lestari Ni Gusti Ayu Made (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
The purpose of this study is to provide an understanding to the wider community regarding the development of early childhood art, especially through the dance activity method. The type of research used is qualitative research. The research location in this research is Banjar Wanasari, Sulangai Village, Petang District, Badung Regency. The time needed in this study was for 3 months of observation when the children were guided to do dance activities. The research subjects in this study were 18 children aged 4-6 years and the object of the research was dance activities and children's art development. Research data was obtained by using interview techniques, using semi-structured interview guidelines. The technique for determining informants in this research is purposive sampling. Based on data analysis using qualitative descriptive research, the results obtained are (1) The form of dance activities to develop early childhood art in Banjar Wanasari, Sulangai Village, Petang District, Badung Regency, is a traditional Balinese dance, which consists of the Panyembrahma dance, Puspanjali dance, dance Rejang Dewa, Pendet Dance, Baris Dance and Kecak Dance. Informants (coaches) chose this dance because the movements in this type of dance are simpler and easier to apply to early childhood. (2) The process of implementing dance activities to develop early childhood art in Banjar Wanasari, Sulangai Village, Petang District, Badung Regency is carried out in 3 stages, namely the preparation stage, implementation stage, and evaluation. (3) Barriers experienced by trainers during dance activities to develop early childhood art are the lack of children's attention to dance activities, lack of discipline in children's dancing activities, lack of children's motivation in dancing activities, children's bodies less flexibility in moving, children less sensitive to the state of the self, and the child's mood changes. Meanwhile, efforts made to deal with these obstacles are to make the atmosphere more interesting, approach children, and provide warm-up.